(untitled) (Update Dental College Journal, 2021)
Background: Trauma-related injuries of the maxillofacial region occur more often these days and dentists are facing this condition frequently in their regular practice life. Traumatic dental injuries affects the same region with different frequencies in different age groups. It should be noted that upper central incisors are mostly traumatized by injuries compare to the other incisors. The maxillary central incisors were about 72%, while premolars, canine, mandibular incisors, the upper lateral incisors injury rate is up to 8%. A strong impact most often affects the crown and a weak and dull impact on the root apical direction and may result in avulsion of tooth and root fracture. Dental injuries caused by trauma have been an emergency condition, treatment options depend on the severity of injuries and clinical condition of the tooth at that moment. Combination treatment for a traumatic fracture of the tooth includes fixation of the tooth, the performance of surgical manipulation, determination of the need for endodontic treatment, restoration, and orthodontic consultations. Problem: In our case patient has an uncomplicated crown fracture. Solution: Direct composite restoration. Update Dent. Coll. j: 2021; 11 (1): 20-22